Digital ethnography of social media: Srikandi Sungai Indonesia activists in water and river conservation - Sri Kusumo Habsari; Fatkhu Rohmatin; Istadiyantha Istadiyantha (Faculty of Social and Political Science, Universitas Airlangga, 2021)
Women have been recognized as environmental activists and having a greater awareness of ecology worldwide since the 19th century. There are many stories of women activists worldwide who have developed significant models for protecting the environment. Social media’s popularity has changed how activists advocate their ideas to generate awareness and environmental protection participation. This study focuses on the grassroots women who join SSI and actively campaign for water and river conservation through social media. It attempts to identify how they use social media to campaign and analyzes their posts’ digital contents to understand their motivation for challenging the water river degradation and their value systems and insights, which drive them to take action. This study considers social media as cultural artifacts and providing spaces for social interaction. The researchers observe SSI’s posting behaviors and identify how they use social media for environmental activism to obtain the data. The finding shows two kinds of women activists join SSI: those who actively involve and participate in the campaign and those who click to support the activities. It also shows that the environmental activist women use social media to communicate their activities rather than maximizing its function to campaign to change the public perspective and attitude concerning the need to take care of the rivers’ water and riverbanks. Women activists continue to adopt dominant Indonesian patterns and social media use orders. Social media’s function is still seen only as a space for selfies rather than to develop a political message concerning environmentalism.